Probability of Burn Victim Survival from BLEVE Fireball Impact during LPG Transportation Accident - Abdul Rashid, Zulkifli; Farhanah Mohd Suhaimi Yeong, Anis; M. Faisal, Nik; Bahari Alias, Azil; Abdulbari Ali, Sherif (International Journal of Engineering and Technology, 2018)
The probability of burn victim survival from BLEVE fireball impacts during an LPG transportation accident can be estimated by understanding the thermal radiation model and the consequences of a BLEVE. The sequence of a BLEVE fireball event is reviewed as guidance in collecting sufficient data and elements to be used throughout this study. The differences between two thermal radiation models which are solid-flame and point-source model have also been distinguished theoretically. Malaysia LPG specification is used to simulate this case study. Thermal radiation by solid-flame model is taken as the main parameter to be compared with few tables, charts and models in determining the consequences of a BLEVE event. Different chances of survival probability are discussed based on a few elements; such as distance, time, age and total burn body surface area.
Keywords: Burn Injury; BLEVE Fireball; Liquefied Petroleum Gas; Simulation; Thermal Radiation.